(untitled) (Central Asian Journal of Medical Sciences, 2019)
Objectives: The aim of our study is to determine intestinal Lactobacillus of relativity healthy adults by colony forming units (CFU) and correlate the link between dairy consumption. Methods: This cross-sectional study was conducted in the city of Ulaanbaatar, Mongolia. A total of 80 healthy Mongolian adults, age 18-70 were recruited between April 2014 and June 2016 in the urban area. Participants self-collected freshly voided feces at home in a sterile container. Results: Of the total of 80 relatively healthy people from 18 to 70 years of age, there were 24 (30%) male and 56 (70%) female participants. By age group; 4 (5%) were age 15-24; 31 (38.7%) were age 25-34; 11 (13.7%) were age 35-44; 14 (17.5%) were age 45- 54; 16 (20%) were age 55-64; 4 (5%) were over 65 years of age. The mean value of colonic Lactobacillus for relatively healthy adults was 1443×104 CFU/ml. Colony forming units of the gut lactobacillus were positively significantly associated with the intake of dairy products per week (r=.400, p<.001). Conclusion: Colonic Lactobacillus of relativity healthy adults was 1443×104 CFU/ml and the colony forming units of Lactobacillus was positively associated with the amount of dairy consumption and types of dairy products in the healthy people.